Potential mosquito vector attraction to- and feeding preferences for pigs in Romanian backyard farms - Stelder, Jonno Jorn; Mihalca, Andrei Daniel; Olesen, Ann Sofie; Kjær, Lene Jung; Boklund, Anette Ella; Rasmussen, Thomas Bruun; Marinov, Mihai; Alexe, Vasile; Balmoş, Oana Maria; Bødker, René (Frontiers in Veterinary Science, 2023)
Mosquitos either biologically or mechanically transmit various vector-borne pathogens affecting pigs. Mosquito species display a wide variety of host preference, as well as host attraction and behaviours. Mosquito species attraction rates to- and feeding rates on pigs or other potential hosts, as well as the seasonal abundance of the mosquito species affects their pathogen transmission potential. We caught mosquitos in experimental cages containing pigs situated in Romanian backyard farms. High feeding preferences for pigs were observed in Aedes vexans (90%), Anopheles maculipennis (80%) and Culiseta annulata (72.7%). However, due to a high abundance in the traps Culex pipiens/torrentium, were responsible for 37.9% of all mosquito bites on pigs in the Romanian backyards, despite low feeding rates on pigs in the cages (18.6%). We also found that other predominantly ornithophilic mosquito species, as well as mosquitos that are already carrying a blood meal from a different (mammalian) host, were attracted to backyard pigs or their enclosure. These results indicate that viraemic blood carrying, for instance, African swine fever virus, West-Nile virus or Japanese encephalitis virus could be introduced to these backyard pig farms and therefore cause an infection, either through subsequent feeding, via ingestion by the pig or by environmental contamination.